Media consumption in Malaysia : a hermeneutics of human behaviour - Wilson, Tony, 1947- (London : Routledge, 2015)
'Focuses upon fundamental axioms in audience and consumer, media and marketing studies in the context of Malaysia. This is a country with a multi-cultural nation, and such diversity in culture proves an intricate culture nuance for the understanding of consumption. The work analyses Chinese, Indian, Indigenous, and Malay Malaysian citizen-consumers immersed in their participatory or promotional media. In Part 1, the author provides a clarifying account of core topics in social media studies. For example, what is the process of authoring (and reading) participatory media such as Twitter? How do promotional video on social media sites like YouTube present a brand's identity? Does engaging with social media emancipate? In the second part of the book, these cultural questions are applied to the situation in Malaysia. Theory is elucidated here by exploring audience narratives as consumers and citizens in Internet genres from chat room (e.g. Messenger) to micro-blogging. Setting mall and media visiting side by side as metaphor and mirror of each other enables a behavioural analysis, shaped by the philosophical psychology of understanding of Heidegger's hermeneutics. Recently rebranded as the'practices perspective' on human activity, this realist model of how we achieve intelligible everyday interaction is closely emulated by other theorists and informs disciplines from business to sociology. Presenting a highly innovative approach to studying the consumption and structuring of media reception and use, this book applies a much more sophisticated variant of phenomenology than is generally invoked in Media Studies, Consumer Studies or related domains'--
Includes bibliographical references : pages 163-188 and index.
Keywords: Mass media -- Social aspects -- Malaysia; Consumer behavior -- Malaysia; Social media -- Malaysia; Marketing -- Social aspects -- Malaysia